Effects of Social Capital and Power on Surviving Transformational Change: The Case of Initial Public Offerings - Fischer, H. M.; Pollock, Timothy G. (Academy of Management Journal, 2004)
We examined how social capital and the power of venture capitalists and founder-CEOs affect IPO firm survival. Using data from 218 U.S. initial public offerings conducted in 1992, we found that average management team tenure and an IPO deal?s network embeddedness decreased the likelihood of failure during a firm?s first five years as a public entity. Founder-CEO presence at the time of an IPO interacted with CEO ownership to decrease the likelihood of failure, and CEO ownership and venture capitalist ownership concentration also decreased that likelihood.